Fundamental Causes and Recommendations for the Insufficient Effectiveness of China’s ’Hierarchical Medical System’ Policy Implementation - Yin, Zihan (International Journal of Social Sciences and Public Administration, 2024)
This paper analyzes sections of China’s official government documents regarding the "hierarchical medical system" policy and compares the implementation of China’s policy with the hierarchical medical policies of the United Kingdom’s National Health Service (NHS). Using the detailed "strengthening the foundation" section in the policy documents as a starting point, the study examines why the issue of "overcrowded major hospitals and underutilized primary healthcare institutions" remains unresolved despite the implementation of the hierarchical medical system policy. One fundamental reason identified is the low competency level of primary care physicians. To address the issue of underqualified primary care physicians, this paper centers on promoting the standardization of primary healthcare and proposes two policy-level recommendations. First, establish a nationwide, objective, and quantitative evaluation standard for the accreditation of primary care physicians, along with a corresponding training system, to standardize the basic diagnostic capabilities of primary healthcare personnel. Second, leverage the medical consortium system to expand career prospects and enhance the professional attractiveness of primary care physicians.